Assessment of crop performance potential using remote sensing - Zmuda, A. D. (Cranfield University, 1992)
This report demonstrates the potential use of optical remote sensing for monitoring the growth and development of winter sown wheat at the field scale. Spectral vegetation indices have been shown to be correlated to important agronomic variables i.e. Leaf Area Index, per cent cover, intercepted solar radiation and grain yield. For winter sown cereals, relationships to grain yield at harvest have been proposed at various times during the growth of the crop. However the precise timing of the remotely sensed input to such models has not received investigation in relation to sowing date, variety and development stage. Further the effect of fungal diseases on such models is not well understood. To address these problems, commercial agronomy trials were used to monitor the reflectance patterns of winter wheat over two growing seasons. During growth and development of the crop, the wheat was destructively sampled and the apex development stage was recorded. Key stages of apex development were found in which spectral data was correlated to grain yield. The relationships were found to be complex in relation to sowing date, variety and fungicide treatment and may therefore not be applicable on a year to year basis.